Heroism Representation of the Antagonist Character in the Film Spider-Man Across the Spider-Verse - Arupanjalu, Gabriel Lintang Jati; Deani Prionazvi Rhizky; Anisa Setya Arifina (Journal Commedies, 2025)
The film Spider-Man: Across the Spider-Verse introduces a new Spider-Man character named Miguel O’Hara (Spider-Man 2099), who embodies heroic values despite being portrayed as a villain. Using Roland Barthes’ semiotics approach, this study analyzes denotation, connotation, and myth within the film. A qualitative research method is employed, utilizing observation and documentation for data collection. The findings reveal that the film highlights Miguel O’Hara’s heroic values, including helping, protecting, bravery, faith, selflessness, strength, moral integrity, and sacrifice. Miguel O’Hara’s character also represents Latin American culture, the ambiguity of heroism, and counter-hegemonic narratives.